The law and custom of the constitution - Anson, William Reynell, 1843-1914; Gwyer, Maurice L. (Maurice Linford); Keith, Arthur Berriedale, 1879-1944 (Oxford : The Clarendon press, 1922)
includes index
I. Parliament. 5th ed. by Maurice L. Gwyer. II. The crown. 4th ed. by A. Berriedale Keith. 2 v.
Keywords: Constitutional law -- Great Britain; Great Britain -- Constitution; Great Britain -- Politics and government